Beneficial Reuse of Municipal Solid Waste Incineration Bottom Slag in Civil Engineering - Xue, M.; Hu, W.; Huanyu, L.; Fu, Y. (Engineering, Technology & Applied Science Research, 2022)
Rapid economic development has caused many disturbing problems in many countries. Waste disposal is a prominent one of those problems. Waste incineration has gradually become the most popular treatment method. Waste incineration has many advantages, such as processing capacity, short period, recycling and utilization of resources, etc., but it also produces a lot of incineration bottom slag. Landfilling is one of the methods for waste incineration bottom slag treatment. However, many domestic waste landfill sites no longer accept incineration bottom slag. Therefore, finding sufficient ways to deal with the incineration bottom slag has become an urgent problem. With the increase of environmental pressure and the development of technology, the beneficial use of incineration bottom slag has been gradually considered. Municipal solid waste incineration bottom slag is an atypical particulate material, similar to some construction materials of civil engineering. For a construction material, basic physical properties and engineering properties are important factors in its performance. However, there is limited research about the engineering performance of incineration bottom slag. The purpose of this paper is to investigate the basic physical and mechanical properties of the incineration bottom slag from one incineration plant in Wuhan and provide a theoretical basis for its application in civil engineering. Through laboratory tests, we found that the incineration slag completely meets the engineering requirements and is harmless to the environment. The incineration bottom slag can be used for road embankment filling, sludge dewatering treatment improvement, landfill site covering, it can substitute aggregates in concrete, etc.